AN AYURVEDIC VIEW OF CERVICAL SPONDYLOSIS AND ITS MANAGEMENT WITH MOCHARASA-SIDDHA TAILA NASYA - Rajashri Adinath Ware; Vinay Ankush Pawar (International Journal of Applied Ayurved Research, 2016)
Cervical spondylosis is a common degenerative condition of the cervical spine. It is most likely caused by age-related changes in the inter-vertebral discs. According to Ayurveda, cervical spondylosis can be considered as Vatavyadhi. It can be correlated with Manyastambha & Vishwachi. Cervical spondylosis is one of the jatrurdhwa vyadhi (diseases above clavicle) and Nasya is explained as the best treatment for jatrurdhwa vyadhi. Efficacy of Mocharasa-siddha tail nasya was assessed in 20 patients showing classical symptoms of cervical spondylosis through single Arm, open labeled, randomized, prospective clinical trial. Shalmali helps to break the pathogenesis of cervical spondylosis. Mocharasa Siddha Taila Nasya showed significant subsides of symptoms in patients which were shown by percentage of relief in symptoms & by statistical analysis which was highly significant. It should be continued to furthermore, to reduce the risk of relapse & severity of cervical spondylosis.